AL- NILAI AL-MA'RŪF DALAM AL-QUR’AN TENTANG PERCERAIAN (Ahkam: Jurnal Hukum Islam, 2022)
Al-Ma'rÅ«f value is a fundamental principle in marriage. Besides, this principle must be also applied in divorce proceeding. This article aims to describe comprehensively about al-ma'rÅ«f in al-Qur'an, therefore the value of the word can be found. This research uses library research that uses a normative approach. This article is analyzed by using al-munÄsabah al-Qur'an theory. This article reveals, there are 10 verses in al-Qur'an containing al-ma'rÅ«f value in theme verses of divorce. These repeated words indicate that al-Qur'an pays attention of al-ma'rÅ«f value seriously in divorce proceeding. This value is sometimes neglected by the husband who divorced her. The outline of this article is, al-ma'rÅ«f value is a treatment that include in frame of Islamic guidance, common senses, compatible with attitude of virtuous people, and appropriate with custom. Al-Ma'rÅ«f value is Islamic guarantee and protection for women, who often get injustice and arbitary. Therefore, it can be concluded that Islam is very much fighting for women's rights, especially in divorce proceeding.